2020
DOI: 10.1007/s13167-020-00226-x
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free nucleic acid patterns in disease prediction and monitoring—hype or hope?

Abstract: Interest in the use of cell-free nucleic acids (CFNAs) as clinical non-invasive biomarker panels for prediction and prevention of multiple diseases has greatly increased over the last decade. Indeed, circulating CFNAs are attributable to many physiological and pathological processes such as imbalanced stress conditions, physical activities, extensive apoptosis of different origin, systemic hypoxic-ischemic events and tumour progression, amongst others. This article highlights the involvement of circulating CFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 240 publications
(258 reference statements)
0
49
0
Order By: Relevance
“…At the level of secondary prevention, cancer patients should undergo predictive diagnostics estimating individual metastatic potential. Recently prominent examples have been presented in the literature [ 164 , 170 , 171 ]. Various carotenoids, including β-carotene, lycopene, and retinoids and their receptors, can effectively fight against premalignant lesions in the role of secondary cancer prevention [ 172 , 173 , 174 , 175 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the level of secondary prevention, cancer patients should undergo predictive diagnostics estimating individual metastatic potential. Recently prominent examples have been presented in the literature [ 164 , 170 , 171 ]. Various carotenoids, including β-carotene, lycopene, and retinoids and their receptors, can effectively fight against premalignant lesions in the role of secondary cancer prevention [ 172 , 173 , 174 , 175 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, predictive machine learning models should be developed that allows for detecting a suboptimal health condition based on voice recordings, ideally in an automated manner using digital biomarkers. C. Follow-up stratification and monitoring of individuals in suboptimal health conditions identified by specialised surveys under point A and/or by AI under point B are recommended utilising disease specific cell-free nucleic acids (cfDNA, ctDNA, mtDNA, miRNA) combined with metabolic patterns detected in body fluids [43,[104][105][106].…”
Section: Pm-related Conclusion and Expert Recommendationsmentioning
confidence: 99%
“…To this end, severely affected cells and tissues intrinsically secrete cell-free nucleic acids [106] such as mitochondrial DNA fragments [107]. It has been demonstrated that COVID-19 patients with increased levels of mtDNA are at elevated death risk, necessity of ICU care and intubation [107].…”
Section: Pm-related Conclusion and Expert Recommendationsmentioning
confidence: 99%
“…Liquid biopsy is a non-invasive or minimally-invasive, cost-effective, painless, precise, and real-time analysis of specific biomarkers obtained from non-solid tissues (biofluids), such as blood, urine, tears, and/or cerebrospinal fluid [ 7 , 8 , 9 , 10 ]. In this review, we discuss the applicability of liquid biopsy to the overall management of mitochondriopathies and disorders known to be associated with mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we discuss the applicability of liquid biopsy to the overall management of mitochondriopathies and disorders known to be associated with mitochondrial dysfunction. Further, based on the accumulated knowledge on the pathomechanisms of mitochondrial injury, we exemplify health conditions that might be involved in the “vicious circle” of mitochondrial damage, which would allow the paradigm shift from reactive measures (treatment of clinically manifested pathologies) to the advanced concepts of predictive approach, targeted prevention, and the personalization of medical services [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%